Developing a Neuronal Differentiation Score for quantitative assessment of glutamatergic differentiation in human neuroblastoma cells - Lina Lin; Wenlong Yan; Enze Zhang; Wenjie Xu; Xiaokai Sui; Hui Zheng; Ting Xiao; Cheng Ni (Tissue and Cell, 2027)

Simulation of equivalent scale-up design of molten salt electrolyzer with stirrer using dimensional analysis and numerical method - Meng Zhang; Lunxiu Cao; Yuannuo Wang; Hemu Zhao; Yi Li; Wenlong Huang; Hongguo Hou; Chunyuan Zhan; Tingting Liu; Jingyang Wang; Rushan Lin; Yu Zhou; et al. (Annals of Nuclear Energy, 2026)

Process-aware SSA-Conv-PatchTST for robust multi-horizon aeration-demand forecasting in full-scale wastewater treatment plants - Ran Song; Xiaole Mei; Xinhua Jiang; Xuelei Ma; Muqier Wudan; Wenlong Bai; Hao Lin; Zhi Li; Shengbin Gao (Journal of Water Process Engineering, 2026)

Synergistic CO2 capture by a novel 2 M 1-(2HE)PP/3 M AEEA blends: Performance evaluation and mechanistic insights - Qixin Li; Dingkai Hu; Haoyang Lin; Dezhi Cao; Yingshuang Zhang; Shaoyun Chen; Wenlong Mo (Journal of Environmental Chemical Engineering, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

Investigating the air cushion effect of side ventilation hole adjustment on water entry impact of concave head vehicles - Zhe Zhang; Zhenyu Xiong; Wenlong Zhuang; Fukui Gao; Zecheng Lin; Guiren Xie; Nana Yang (Ocean Engineering, 2026)

Moderate thermal-chemical-enzymatic pretreatment for waste activated sludge: Methane yield enhancement and life cycle assessment - Wenlong Zhu; Lin Zhu; Xiangwu Yao; Taolve Chi; Fangyuan Cui; Caokun Li; Yisong Feng; Baolan Hu (Environmental Research, 2026)

Crystalline 2D aromatic polyimine with deep-band for efficient capacitive energy storage - Lichuan Jia; Xiquan Xiao; Zhixing Wang; Wenlong Lin; Mengzhou Liao; Hongli Yang; Ling Xu; Hua-Dong Huang; Shengyang Zhou; Zhong-Ming Li (Chemical Engineering Journal, 2026)

Intracranial Mitochondrial Microparticles Promote Cerebral Edema via Endothelial Injury in Stroke - Xiaoyan Du; Xintong Yu; Mengfei Wang; Ying Fu; Kunxin Lin; Jiaying Wu; Qianqian Lin; Wenlong Zhao; Yi Lin (Translational Stroke Research, 2026)

Optimizing carbon-cement electrode performance through construction of a strong skeleton-highly connected pore structure based on ettringite - Xiang Lin; Xujiang Wang; Guanjie He; Jian Song; Yanmei Cheng; Jie Chen; Xin Shu; Deqiang Sun; Jingwei Li; Zhijuan Hu; Wenlong Wang (Chemical Engineering Journal, 2026)

Facilitating extracellular respiration of Methanosarcina barkeri with magnetite nanoparticle: Formation of conductive magnetite nanoparticle-membrane complex - Wenlong Lin; Junzhe Zhang; Lianfu Liang; Yang Li; Zhiqiang Zhao; Yaobin Zhang (Bioresource Technology, 2026)

A molecular study of synergistic inhibition of methane hydrate growth with glycine-based peptides and PVCap - Huiyun Mu; Yang Liu; Lin Ding; Wenlong Wang; Xiaofang Lv; Yisong Yu; Qianli Ma; Chuanshuo Wang; Xiaoyan Li; Shidong Zhou (Fuel, 2026)

Film matrix modification synergize with active ingredient introduction strategy to synthesize polysaccharide-based active packaging with enhanced barrier performance and functional activity for efficient perishable fruit preservation - Zitian Liu; Ligang Lin; Jiaxin Zhang; Kui Niu; Minglun Cheng; Yuxuan Zhu; Bin Du; Wenlong Hou; Huiyang Shang (Food Hydrocolloids, 2026)

Prediction of clock bias for BeiDou satellites using a combination of variational mode decomposition and long short-term memory network - Wenlong Sun; Fengfeng Shi; Yuting Lin; Jinfeng Xu; Guojun Li; Guocheng Wang; Shaofeng He; Jiawei Yu; Pei Ma (Journal of Geodesy, 2026)

DlNAC41 and DlNAC100 transcription factors modulate longan pulp breakdown via adjusting the expression of cell wall degradation-related genes - Hui Wang; Wenlong Zhou; Xinyue Mu; Zhongqi Fan; Ruiling Zhuo; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

Co-exposure to Cadmium and Polystyrene Nanoplastics Intensifies Renal Damage in Mice via the Activation of the PANoptosis Pathway - Rongmei Wang; Hao Xi; Ting Ma; Jingbo Lin; Huifeng Shi; Yanming Cai; Cuiyan Zhao; Wenlong Yan (Biological Trace Element Research, 2026)

Characteristics of phosphorus-solubilizing bacteria and mediated phosphorus cycle in sediments of urban river-lake interfaces - Yi Li; Xiaoxi Li; Lihua Niu; Jiaxin Hu; Wenlong Zhang; Li Lin; Wenming Zhang (Water Research, 2026)

Mechanism of the changes in pore water components and pore size of aeolian sand during freeze–thaw cycles on the Qinghai-Xizang Plateau - Wenlong Ma; Lin Chen; Xiyin Zhang; Lianhai Zhang; Zhuangzhuang Liu; Haikun Qin (Journal of Hydrology, 2026)

Nickel-based spinel-modified multi-dimensional pore molecular sieves co-catalyze the directional preparation of aromatics from lignin pyrolysis - Wenlong Gao; Jinpeng Wei; Yuyu Wang; Yulong Ma; Fei Pan; Feng Lin; Wenxin Ji; Yuanyuan Li; Yonggang Sun (Fuel, 2026)

SNX25-mediated regulation of NGF by Periploca sepium periplosides from Xiangjiapi in macrophage-dependent anti-nociception - Yuan Chang; Mengru Guo; Wenlong Yuan; Yong Hu; Fenghua Zhu; Xiaoqian Yang; Weimin Zhao; Dongyi He; Shijun He; Jianping Zuo; Zemin Lin (Science China Life Sciences, 2026)

Rural Community Resilience to Drought and Sustainable Development in Inner Mongolian Plateau, China - Wenlong Li; Rui Xu; Haiying Lin; Fujia Li (Chinese Geographical Science, 2026)

Study on the ground-air temperature relationship under microenvironmental differences in the warm permafrost region of the Tibetan Plateau - Nuocheng Li; Zhanju Lin; Xingwen Fan; Yanhe Wang; Wenjiao Li; Qiang Gu; Wenlong Pang; Xuhui Wang; Peng Zhang (Cold Regions Science and Technology, 2026)

Mitigation of focused wave effects on the box girder coastal bridge using floating breakwaters and frictional rubber bearings - Lin Li; Bo Huang; Wenlong Luo; Shixiao Fan (Ocean Engineering, 2025)

Elevated blood microplastics and their potential association with Parkinson’s disease - Zongtang Xu; Xingting Huang; Ziting Zhu; Fengchu Liang; Huimin Hu; Tingting Cai; Tianni Liu; Weiqing Huang; Lin Lu; Pingyi Xu; Wenlong Zhang (Journal of Hazardous Materials, 2025)

Effects of reductive soil disinfestation on remediating microplastic-polluted soils and restructuring microbial communities - Haoxue Liu; Lin Dong; Xinjie Wang; Yu Sun; Kunshuo Yang; Enqing Chen; Wenlong Song; Lei Zhang (Journal of Environmental Chemical Engineering, 2025)

A multi-task deep attention network for simultaneous rapid quantification of sucrose, glucose, and fructose contents in pumpkin using FT-NIR spectroscopy - Yingchao Xu; Jiayu Luo; Shudan Xue; Huihui Han; Wenlong Luo; Wenjun Liu; Qingmin Jin; Huijing Lin; Baoling Chen; Yingyin Lin; Rong Zhang; Yujuan Zhong (Food Chemistry, 2025)

Phase transformation toughening behaviors of t-ZrO2 nanoparticles in glass sealing of YSZ ceramic and Crofer22H stainless steel for solid oxide fuel cell - Wei Cong; Yangfan Fu; Peng He; Tiesong Lin; Guangjie Feng; Zhanpeng Zhang; Wenlong Duan; Yifeng Wang; Qian Wang (Chemical Engineering Journal, 2025)

Catalytic depolymerization of authentic lignin via polymetallic modular active frameworks engineered toward value-added phenolic chemicals - Fei Pan; Yuyu Wang; Jinpeng Wei; Yulong Ma; Wenlong Gao; Feng Lin; Wenxin Ji; Yuanyuan Li; Yonggang Sun (Journal of Environmental Chemical Engineering, 2025)

Chitosan-based Janus dressing with asymmetric wettability for rapid hemostasis, antibacterial protection, and tissue regeneration in hemorrhagic wound management - Jiyuan Wang; Haowen Ye; Kaitong He; Weikang Jiang; Wei Lan; Zu’an Zeng; Peiran Lin; Han Wang; Botao Gao; Wenlong Wang; Yadong Tang (Carbohydrate Polymers, 2025)

Functional and microbial insights into the gill symbiosis and metal tolerance of the cold seep mussel Gigantidas haimaensis - Xuanguang Liang; Mingmin Du; Yuxin Qin; Wenlong Cai; Junrou Huang; Genmei Lin; Jianguo Lu (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Exploration on using solid waste-derived sulphoaluminate composite as low-cost binder for high-impermeability stabilization of sandy soil - Shuang Zhang; Jingwei Li; Wenbin Shi; Fawei Lin; Bigaliev Aitkhazha Bigalievich; Eminov Ashraf Mamurovich; Wenlong Wang (Waste Disposal & Sustainable Energy, 2025)

Pathogenic Ralstonia solanacearum in Agriculture: A Review of Prevention and Control Strategies Based on Natural Products - Lin Jiang; Zixian Zeng; Amanpreet Kaur; Wenlong Yang; Huaxue Huang; Shunxiang Li; Sai Jiang (Current Microbiology, 2025)

Flexible and cleaner alkaloid extraction of Sophora Flavescens and Heterosmilax Japonica with the aid of process analytical technology - Liping Liu; Lin Miao; Wenlong Li; Tongchuan Suo (Sustainable Chemistry and Pharmacy, 2025)

Estimation of rice yield using multi-source remote sensing data combined with crop growth model and deep learning algorithm - Jian Lu; Jian Li; Hongkun Fu; Wenlong Zou; Junrui Kang; Haiwei Yu; Xinglei Lin (Agricultural and Forest Meteorology, 2025)

Honey-processed Astragalus polysaccharides exhibit enhanced Qi-tonifying effects via structural modifications and microbiome-metabolome regulation - Zhaohui Lin; Lili Lu; Wenlong Guo; Shuyu Han; Yufei Tian; Hongyuan Chen; Wen Rui (Food Bioscience, 2025)

Identification of Chlortetracycline Hydrochloride as a Antibacterial Compound Against Pseudomonas syringae pv. tomato DC3000 Through Natural Products Library Screening - Lin Jiang; Linghe Huang; Yajing Wang; Jing Li; Zixian Zeng; Wenlong Yang; Sai Jiang; Dousheng Wu; Zhi Wang; Shunxiang Li; Yanxia Huang; Hong Pu (Current Microbiology, 2025)

Anisotropic deposition of Cu2(OH)3Cl: The critical role of enclosed pit formation heterogeneity - Qihao Lin; Guoqing Chen; Shiwen Zou; Wenlong Zhou; Yufei Zu; Xuesong Fu (Chemical Engineering Journal, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

The plant retromer components SNXs bind to ATG8 and CLASP to mediate autophagosome movement along microtubules - Yanglan Liao; Xibao Li; Wenlong Ma; Xinyi Lin; Jiayi Kuang; Xuanang Zheng; Zien Li; Fanfan Qiao; Chuanliang Liu; Jun Zhou; Faqiang Li; Ruixi Li; et al. (Molecular Plant, 2025)

Progressive-composition-transformation-induced enhanced hyperthermia-based nanozyme towards long-lasting and complete therapy of cancer - Wenlong Zhang; Di Sun; Bin Yang; Jiaqi Liu; Yilin Yuan; Dezhuang Li; Yuliang Sun; Guoqiang Guan; Yanli Liu; Dapeng Wu; Hong Liao; Juntang Lin; et al. (Chemical Engineering Journal, 2025)

Study of the Drug Resistance Function of Ivermectin-Resistance-Related miRNAs in Haemonchus contortus - HaiFeng Wen; YanMin Zhang; Lin Yang; WenLong Wang; ChunXia Liu (Acta Parasitologica, 2025)

Multifunctional nanofiber system with photothermal-controlled drug delivery and motion monitoring capabilities as intelligent wound dressing - Peiran Lin; Kaitong He; Jiahui Luo; Jiyuan Wang; Yuting Liu; Jian Zhang; Hao Fan; Shunfen Huang; Wei Lan; Wenlong Wang; Xuhui Zhang; Botao Gao; et al. (Chemical Engineering Journal, 2025)

Strong and tough anisotropic short-chain chitosan-based hydrogels with optimized sensing properties for flexible strain sensors - Huijuan Lin; Wenlong Yuan; Wencan Zhang; Rao Dai; Tian Zhang; Yueyun Li; Shuanhong Ma; Shasha Song (Carbohydrate Polymers, 2025)

Clock bias prediction of navigation satellite based on BWO-CNN-BiGRU-attention model - Wenlong Sun; Jinping Chen; Caibo Hu; Yongxin Lin; Maolei Wang; He Zhao; Run Zhao; Guitao Fu; Tan Zhao (GPS Solutions, 2025)

HZSM-5 supported with N-doped Fe for microwave catalytic pyrolysis of lignin - Yan Wang; Kangqi Cao; Wenlong Sun; Xiangxi Lin; Jianwei Wang; Jessica Villarreal; Longzhi Li (Chemical Engineering Journal, 2024)

Efficient and selective upgrading of biomass-derived furfural into 1,5 pentanediol by Co2+ etched ZIF-8 derived ZnCo layered double hydroxides nanoflake - Ye Tian; Wenlong Xie; Zihao Yang; Zhendong Yu; Renjie Huang; Lin Luo; Miao Zuo; Zheng Li; Lu Lin; Xianhai Zeng (Chemical Engineering Journal, 2024)

Intelligent chemical profiling of 73 edible flowers by liquid chromatography-high resolution mass spectrometry combined with HRMS database and their authentication based on large-scale fingerprints - Ziqing Li; Jianqing Zhang; Lin Yang; Xiaolan Li; Qian Meng; Yun Li; Shuai Yao; Wenlong Wei; Qirui Bi; Hua Qu; Yaling An; De-an Guo (Food Chemistry, 2024)

Critical review for the potential analysis of material utilization from inorganic industrial solid waste - Xuan Guo; Menglan Zeng; Hongdi Yu; Fawei Lin; Jingwei Li; Wenlong Wang; Guanyi Chen (Journal of Cleaner Production, 2024)

Intrinsically stretchable jellyfish-like gold nanowires film as multifunctional wearable chemical and physical sensors - Heng Zhang; Fenge Lin; Gangsheng Chen; Cheng Yang; Hanqiang Zhang; Mengwen Yan; Heng Li; Xi Wang; Wenlong Cheng; Yi Chen (Chemical Engineering Journal, 2024)

PLD2 deletion ameliorates sepsis-induced cardiomyopathy by suppressing cardiomyocyte pyroptosis via the NLRP3/caspase 1/GSDMD pathway - Jun Li; Da Teng; Wenjuan Jia; Lei Gong; Haibin Dong; Chunxiao Wang; Lihui Zhang; Bowen Xu; Wenlong Wang; Lin Zhong; Jianxun Wang; Jun Yang (Inflammation Research, 2024)
Objective Sepsis-induced cardiomyopathy (SICM) is a life-threatening complication. Phospholipase D2 (PLD2) is crucial in mediating inflammatory reactions and is associated with the prognosis of patients with sepsis. Whether PLD2 is involved in the pathophysiology of SICM remains unknown. This study aimed to investigate the effect of PLD2 knockout on SICM and to explore potential mechanisms. Methods The SICM model was established using cecal ligation and puncture in wild-type and PLD2-knockout mice and lipopolysaccharide (LPS)-induced H9C2 cardiomyocytes. Transfection with PLD2-shRNA lentivirus and a PLD2 overexpression plasmid were used to interfere with PLD2 expression in H9C2 cells. Cardiac pathological alterations, cardiac function, markers of myocardial injury, and inflammatory factors were used to evaluate the SICM model. The expression of pyroptosis-related proteins (NLRP3, cleaved caspase 1, and GSDMD-N) was assessed using western blotting, immunofluorescence, and immunohistochemistry. Results SICM mice had myocardial tissue damage, increased inflammatory response, and impaired heart function, accompanied by elevated PLD2 expression. PLD2 deletion improved cardiac histological changes, mitigated cTNI production, and enhanced the survival of the SICM mice. Compared with controls, PLD2-knockdown H9C2 exhibits a decrease in inflammatory markers and lactate dehydrogenase production, and scanning electron microscopy results suggest that pyroptosis may be involved. The overexpression of PLD2 increased the expression of NLRP3 in cardiomyocytes. In addition, PLD2 deletion decreased the expression of pyroptosis-related proteins in SICM mice and LPS-induced H9C2 cells. Conclusion PLD2 deletion is involved in SICM pathogenesis and is associated with the inhibition of the myocardial inflammatory response and pyroptosis through the NLRP3/caspase 1/GSDMD pathway.

Efficient energy transport from triboelectric nanogenerators to lithium-ion batteries via releasing electrostatic energy instantaneously - Xinyuan Li; Yikui Gao; Yuexiao Hu; Liang Lu; Zhihao Zhao; Wenlong Ma; Wenyan Qiao; Xiaoru Liu; Zhong Lin Wang; Jie Wang (Chemical Engineering Journal, 2024)

Mechanical properties and constitutive model of high-abundance methane hydrates containing clayey–silt sediments - Fan Yang; Changjun Li; Na Wei; Wenlong Jia; Jie He; Shuoshuo Song; Yuanrui Zhang; Youzhi Lin (Ocean Engineering, 2024)

Occurrence of Cladosporium herbarum causing leaf spot on Avena sativa in China - Jiangui Zhang; Guiqin Zhao; Jikuan Chai; Liang Zeng; Wenlong Gong; Fu Ran; Xiumei Nie; Ruifang Zhang; Doudou Lin (Crop Protection, 2024)

Transition of organic matter from allochthonous to autochthonous alters benthic nutrient dynamics via microbial food webs - Nan Yang; Yi Li; Li Lin; Lihua Niu; Wenlong Zhang; Longfei Wang (Science of The Total Environment, 2024)

Risk of papillary thyroid carcinoma and nodular goiter associated with exposure to semi-volatile organic compounds: A multi-pollutant assessment based on machine learning algorithms - Fei Wang; Yuanxin Lin; Jianing Xu; Fugui Wei; Simei Huang; Shifeng Wen; Huijiao Zhou; Yuwei Jiang; Haoyu Wang; Wenlong Ling; Xiangzhi Li; Xiaobo Yang (Science of The Total Environment, 2024)

Characterization of methyltetrahydrophthalic anhydride esterified corn starch and their ability in stabilizing Pickering emulsion - Yang Zhong; Yi Lin; Mingxing Yang; Xiaodan Zeng; Dayu Liu; Wenlong Liu; Weijun Chen (Journal of Food Engineering, 2024)

Effect of different operation conditions on PCDD/F inhibition by ammonium dihydrogen phosphate: concentrations, distributions and mechanisms - Jiayao Wu; Weican Xiang; Xiaoxiao Wang; Wenlong Song; Yuxuan Ying; Xiaoqing Lin; Xiaodong Li (Waste Disposal & Sustainable Energy, 2024)

Identification and molecular mapping of a major gene conferring resistance to Phytophthora sansomeana in soybean ‘Colfax’ - Feng Lin; Muhammad Salman; Zhanguo Zhang; Austin G. McCoy; Wenlong Li; Raju Thada Magar; Drew Mitchell; Meixia Zhao; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2024)

Association of residential greenness, air pollution with adverse birth outcomes: Results from 61,762 mother‑neonatal pairs in project ELEFANT (2011–2021) - Yuanyuan Yu; Huishu Lin; Qisijing Liu; Yuxuan Ma; Lei Zhao; Weixia Li; Yan Zhou; Hyang-Min Byun; Penghui Li; Chen Li; Congcong Sun; Xuemei Chen; et al. (Science of The Total Environment, 2024)

A novel integrated automatic strategy for amino acid composition analysis of seeds from 67 species - Yelin Ding; Qirui Bi; Dongdong Huang; Jingmei Liao; Lin Yang; Xiaoxiao Luo; Peilei Yang; Yun Li; Changliang Yao; Wenlong Wei; Jianqing Zhang; Jiayuan Li; et al. (Food Chemistry, 2023)

Spatial-temporal evolution of urban form resilience to climate disturbance in adaptive cycle: A case study of Changchun city - Wenlong Xie; Cheng Sun; Zhongjie Lin (Urban Climate, 2023)

Vulnerability of farmers and herdsmen households in Inner Mongolian plateau to arid climate disasters and their development model - Wenlong Li; Suocheng Dong; Haiying Lin; Fujia Li; Hao Cheng; Zhuang Jin; Shan Wang; Hasbaggen Zhang; Pengshen Hou; Bing Xia (Journal of Cleaner Production, 2023)

The content and distribution of 18 phenolic compounds in 462 batches of edible flowers from 73 species commercially available in China - Ziqing Li; Jianqing Zhang; Qian Meng; Lin Yang; Mingyang Qiu; Yun Li; Shuai Yao; Wenlong Wei; Changliang Yao; Qirui Bi; Jiayuan Li; De-an Guo (Food Research International, 2023)

Performance of Sludge in the UASB Reactor for Treating Sulfate Wastewater: Sulfate Removal and Changes in the Community Structure Before and After Reaction - Liping Niu; Shuang Sun; Fangying Yu; Xinyue Zhang; Shiying Fan; Yue Sun; Wenlong Lin; Bowen Wang; Xingde Zhang (Water, Air, & Soil Pollution, 2023)

A novel BC/g-C3N4 porous hydrogel carrier used in intimately coupled photocatalysis and biodegradation system for efficient removal of tetracycline hydrochloride in water - Huanjun Zhang; Yanan Yu; Yi Li; Li Lin; Chi Zhang; Wenlong Zhang; Longfei Wang; Lihua Niu (Chemosphere, 2023)

Isotopic characteristics and sources of suspended particulate organic matter in a reservoir of Chinese desert grassland areas: the influence of dry and wet seasons and the role of atmospheric deposition - Xiaojing Zhang; Shengwei Zhang; Junping Lu; Ruishen Li; Xi Lin; Wenlong Gao (Environmental Science and Pollution Research, 2023)

Insight into the Co2+/Co3+ sites for the selective reduction of furfural to furfuryl alcohol - Jiahong Chen; Wenlong Jia; Xin Yu; Yong Sun; Jiaren Zhang; Shuliang Yang; Xing Tang; Lincai Peng; Xianhai Zeng; Lu Lin (Fuel, 2023)

Measurement and identification of relative poverty level of pastoral areas: an analysis based on spatial layout - Haiying Lin; Youhan Gao; Tianqi Zhu; Huayuan Wu; Pengshen Hou; Wenlong Li; Shuxia Hou; Muhammad Umer Arshad (Environmental Science and Pollution Research, 2022)
Pastoral areas are the key difficulty in China’s pursuit of common prosperity and a key region for China to build the northern ecological safety barrier and to realize the Two Centenary Goals. It is of great significance to scientifically evaluate the quality of rural life (QRL), measure the relative poverty level (RPL), and identify the relatively poor areas, making it possible to dock poverty elimination with rural revitalization. Based on the socio-economic data of 18 pastoral areas in Inner Mongolia, this paper draws on spatial layout theory to evaluate QRL and measures RPL by the natural breakpoint method and then identifies the relatively poor areas in Inner Mongolia. The results show that (1) the QRLs of pastoral areas in Inner Mongolia were unbalanced and highly polarized. The mean score of QRLs was 0.2598. Eleven (61.11%) of the counties/banners had a QRL smaller than the mean score. On the spatial layout of QRLs, the western areas were stronger than the central areas. High QRL counties/banners are mainly concentrated in the western region. In the central region, the QRLs were very fragmented, falling onto all five levels. (2) The pastoral areas in Inner Mongolia differed significantly in RPL. The mean score of RPL stood at 0.3788. Nine counties/banners (50%) had an RPL greater than the mean. Contrary to the spatial layout features of QRLs, the central pastoral areas in Inner Mongolia had stronger RPLs than the eastern ones. High RPL counties/banners are mostly clustered in the central region. The spatial layout of RPLs is relatively reasonable in the central region: the RPLs decreased gradually from Dorbod Banner. (3) Nearly 45% of the pastoral areas in central and western Inner Mongolia face serious relative poverty and a high risk of returning to poverty. Eight counties/banners (45%) were identified as high composite relative poverty areas. From spatial layout, the composite relatively poor counties/banners clustered clearly, mainly in the western region. Finally, this paper establishes a warning mechanism against large-scale returning to poverty, aiming to lower composite RPL. The research results provide empirical reference and implementation path for consolidating the results of poverty eradication and facilitating rural revitalization.

Identification and characterization of pleiotropic and epistatic QDRL conferring partial resistance to Pythium irregulare and P. sylvaticum in soybean - Feng Lin; Wenlong Li; Austin G. McCoy; Kelly Wang; Janette Jacobs; Na Zhang; Xiaobo Huo; Shabir H. Wani; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2022)

Characterizing sediment bacterial community and identifying the biological indicators in a seawater-freshwater transition zone during the wet and dry seasons - Yongbin Li; Duanyi Huang; Weimin Sun; Xiaoxu Sun; Geng Yan; Wenlong Gao; Hanzhi Lin (Environmental Science and Pollution Research, 2022)

Effects of Diversion Wall on the Hydrodynamics and Withdrawal Sediment of A Lateral Intake - Wenlong Zhao; Jian Zhang; Wei He; Lin shi; Xuyun Chen (Water Resources Management, 2022)

Overall and central obesity and prostate cancer risk in African men - Ilir Agalliu; Wei-Kaung Jerry Lin; Janice S. Zhang; Judith S. Jacobson; Thomas E. Rohan; Ben Adusei; Nana Yaa F. Snyper; Caroline Andrews; Elkhansa Sidahmed; James E. Mensah; Richard Biritwum; Andrew A. Adjei; et al. (Cancer Causes & Control, 2022)

Citric acid and AMF inoculation combination–assisted phytoextraction of vanadium (V) by Medicago sativa in V mining contaminated soil - Lang Qiu; Wenlong Gao; Zhigang Wang; Baoqin Li; Weimin Sun; Pin Gao; Xiaoxu Sun; Benru Song; Yanxu Zhang; Tianle Kong; Hanzhi Lin (Environmental Science and Pollution Research, 2021)

Identification of a major QTL related to resistance to soybean mosaic virus in diverse soybean genetic populations - Jiahao Chu; Wenlong Li; Dongri Piao; Feng Lin; Xiaobo Huo; Hua Zhang; Hui Du; Youbin Kong; Yuan Jin; Xihuan Li; Caiying Zhang (Euphytica, 2021)

Molecular mapping of quantitative disease resistance loci for soybean partial resistance to Phytophthora sansomeana - Feng Lin; Wenlong Li; Austin G. McCoy; Xuan Gao; Paul J. Collins; Na Zhang; Zixiang Wen; Sizhe Cao; Shabir H. Wani; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2021)

Analysis of stability of the Baihetan arch dam based on the comprehensive method - Wenlong Lyu; Lin Zhang; Baoquan Yang; Yuan Chen (Bulletin of Engineering Geology and the Environment, 2021)

Analysis of Cerebrospinal Fluid Soluble TREM2 and Polymorphisms in Sporadic Parkinson’s Disease in a Chinese Population - Guoyou Peng; Jiewen Qiu; Hanqun Liu; Miaomiao Zhou; Shuxuan Huang; Wenyuan Guo; Yuwan Lin; Xiang Chen; Zhe Li; Guihua Li; Wenlong Zhang; Yunlong Zhang; et al. (Journal of Molecular Neuroscience, 2020)

Development and application of EST–SSRs markers for analysis of genetic diversity in erect milkvetch (Astragalus adsurgens Pall.) - Wenlong Gong; Lin Ma; Pan Gong; Xiqiang Liu; Zan Wang; Guiqin Zhao (Molecular Biology Reports, 2019)

A complete mitochondrial genome of wheat (Triticum aestivum cv. Chinese Yumai), and fast evolving mitochondrial genes in higher plants - Peng Cui; Huitao Liu; Qiang Lin; Feng Ding; Guoyin Zhuo; Songnian Hu; Dongcheng Liu; Wenlong Yang; Kehui Zhan; Aimin Zhang; Jun Yu (Journal of Genetics, 2009)